1986
DOI: 10.2186/jjps.30.387
|View full text |Cite
|
Sign up to set email alerts
|

A basic study on visible light resin for denture base. Part 1. The property of mechanisum.

Abstract: Heat-curing resin is mainly used as denture base materials. But, recently, visible light curing resin and its curing unit have been developed by Dentsply Co. to be on the market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A series of basic studies on visible light-curing denture base resin manufactured by Dentsply Co. Ltd. was performed [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A series of basic studies on visible light-curing denture base resin manufactured by Dentsply Co. Ltd. was performed [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have hitherto reported a series of basic studies on light-curing resin for use as a denture base in order to evaluate its clinical application [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%